Comparison of methods to determine total edible meat in the male Holstein cattle carcass (2013)
ABSTRACT: the objective of beef cattle farming is to produce young animals with adequate proportions of meat, fat and bone. In many countries, including Colombia, research on carcass quality and performance has focused on Bos indicus, resulting in little information available on Bos taurus breeds, particularly Holstein. Objective: to compare several methods for determining total edible meat (TEM) in the carcass of intact Holstein males slaughtered at 330 kg and 26 months of age. Methods: the TEM was determined by the direct method (true-TEM), and also by two indirect methods based on equations. One equation involving carcass measurements was proposed by the Instituto de Ciencia y Tecnología de Alimentos (ICTA). The other equation is based on the muscle proportion between ribs 9-11. Results: variance analysis detected statistically significant difference (p < 0.05) among all methods. The relationship between true-TEM and that estimated by indirect methods was high (r = 0.9756). However, according to Bland-Altman interchangeability analysis, the direct method is not interchangeable with the prediction by ICTA. The TEM variability obtained by the three methods was similar (average CV = 18.15%). Conclusion: according to this study, the method based on the muscle proportion between ribs 9-11 is useful for estimating TEM in Holstein bull carcasses.